Virtual screening of co-formers for ketoprofen co-crystallization and the molecular properties of the co-crystal - S. Siswandi & , Taofik Rusdiana, Jutti Levita (Journal of Applied Pharmaceutical Science, 2015)
Ketoprofen or [2-(3-benzoylphenyl)propionic acid] is a nonsteroidal antiinflammatory and analgesic agent. The positive qualities of ketoprofen are based on optimal physicochemical and structural characteristics, its ability to penetrate into and accumulate in the inflammation centers and compatibility with other classes of drugs. This compound is practically insoluble in water, therefore as most of NSAID drugs, it is categorized as Biopharmaceutics Classification System (BCS) class II. A widely used to enhance the solubility of poorly water soluble drugs is co-crystallization. A co-crystal is a multi-component crystal which involves non-covalent interactions between API and its co-formers. In this work, we developed virtual screening of co-formers for ketoprofen by employing molecular docking method. AutoDock was used for docking. Parameters observed were type and energy (Ei) of interaction. The work was continued by co-crystallization process and solubility assay of the mixtures according to Higuchi and Connor method using UV spectrophotometer. Based on molecular docking, the best co-former is saccharin (Ei = -3.14 kcal/mol). The docking result fits the solubility assay of the ketoprofen-saccharin co-crystal (300.62 μg/mL in water or 256.54% increasing of solubility compared to ketoprofen). Ketoprofen co-crystal shows better curve (90.15 % in 60 minutes) than ketoprofen (78.87 % in 60 minutes). Co-crystallization of ketoprofen with saccharin increases the dissolution profile of ketoprofen.
Keywords: Anti-inflammatory agent, co-crystal, co-former,ketoprofen, molecular docking, saccharin.